Protective effect of Bletilla ochracea Schltr. against acetogenic gastric ulcer in rats based on non-targeted metabolomics - Fang, Rongze; Zeng, Qi; Tang, Xiusheng (Frontiers in Medicine, 2024)
Background: Gastric ulcer (GU), a globally prevalent disease, represents a significant burden to human health. Bletilla ochracea Schltr. (BOS), an herbal medicine, shows promising therapeutic potential in the treatment of chronic GU.This study utilized a rat model of chronic gastric ulceration induced by acetic acid to evaluate the protective effects of Bletilla ochracea Schltr. (BOS) on gastric tissue through the analysis of gross morphological and histopathological changes. Non-targeted metabolomic techniques were employed to identify differential metabolites, followed by the use of metabolic analysis software to enrich the pathways associated with these metabolites, thereby revealing the potential mechanisms underlying the anti-gastric ulcer effects of BOS.The results suggest that the primary mechanism underlying BOS regulation of GU involves modulation of endogenous metabolites, including dimethylglycine, L-2,4-diaminobutyric acid, uridine propionic acid and L-asparagine. These diverse metabolites may have anti-inflammatory, antioxidant and reparative properties. In addition, KEGG enrichment analysis indicated potential anti-GU effects of BOS through diverse pathways such as energy metabolism, immune metabolism and amino acid metabolism.The study demonstrates BOS protective effects on GU in rats, potentially through modulating key metabolites and pathways, highlighting its therapeutic potential and warranting further investigation for clinical applications.